First Report of Equine Leishmaniosis in the State of Sergipe, Brazil - Gonçalves, Saulo Romero Felix; Waterloo, Mateus de Melo Lima; Barretto, Mariana Lumack de Monte; Moura, João Paulo Gonçalves; Oliveira, Andrea Alice da Fonseca; Silva, Jacilene Lourenço da; Silva Junior, Valdemiro Amaro da (Acta Scientiae Veterinariae, 2020)
Background: Leishmaniasis is caused by an obligate intracellular protozoan of the genus Leishmania. In Brazil, the species Leishmania (Leishmania) infantum is reported as an etiological agent of leishmaniasis. Transmission of the disease occurs through bite of the sand fly mosquitoes Lutzomyia longipalpis and Lutzomyia cruzi, present in several regions of Brazil, including the state of Sergipe, where they are considered endemic. Although few cases have been reported in other states of Brazil, no case of cutaneous leishmaniasis in horses has been reported in Sergipe. The objective of this study was to report a case of cutaneous leishmaniasis in a horse in the municipality of Itaporanga d’Ajuda, Sergipe, Brazil. Case: A 2-year-old female quarter-horse was examined by a private veterinarian due to the presence of a nodular lesion on the mucocutaneous region of the lips. Macroscopically, the nodule was alopecic with depigmented areas, measuring approximately 1.0 cm in diameter, and there was a focal ulcer in the region of the labial commissure. Excisional biopsy was performed as follows; the material obtained was fixed in 10% buffered formalin and sent for histopathological examination. Further, it was subjected to routine histological processing by embedment in paraffin and hematoxylin-eosin staining. Microscopically, there were intense multifocal to coalescent lymphohistioplasmocytic infiltrates with epithelioid macrophages and multinucleated giant cells, both containing amastigote forms comparable with Leishmania spp. Morphological diagnosis was defined as extensive multifocal to coalescent chronic granulomatous dermatitis with intracytoplasmic amastigote forms. Furthermore, for positive controls, immunohistochemical examination was performed using serum from dogs naturally infected with L. (L.) infantum, which resulted in a strongly positive immunostaining of innumerable intracytoplasmic amastigote structures, confirming infection by Leishmania infantum. Discussion: Leishmaniasis is a public health problem and is frequently studied. In the biological cycle of the parasite, canids are considered as reservoirs, and humans are considered as accidental hosts. However, in endemic rural areas, several species of mammals can be infected. Microscopic lesions of cutaneous leishmaniasis are compatible with granulomatous dermatitis, characterized by lymphohistioplasmocytic inflammatory infiltrates with epithelioid macrophages containing amastigote forms. Age, breed, and sex are not considered predisposing factors for this disease and their transmission depends on the existence of the vector in the environment. The diagnosis is based on serological, molecular, and immunohistochemical techniques; in the present study, immunohistochemistry was performed for diagnostic confirmation using serum from dogs naturally infected with L. (L.) infantum. It was found that this antibody can be successfully applied in the immunohistochemical diagnosis of leishmaniasis in tissues of horses. Histopathological examination including immunohistochemical analysis was essential to confirm the diagnosis. To the best of our knowledge, this is the first report of Leishmania infantum infection in a horse in the state of Sergipe, Brazil. It is essential to carry out epidemiological studies to define control measures to be implemented in the state since it is important for public health.